2022
DOI: 10.1021/acs.jcim.2c00126
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Vibrational Entropy Assessment and Analysis of SARS CoV-2 Main Protease

Abstract: The three-dimensional conformations of a protein influence its function and select for the ligands it can interact with. The total free energy change during protein–ligand complex formation includes enthalphic and entropic components, which together report on the binding affinity and conformational states of the complex. However, determining the entropic contribution is computationally burdensome. Here, we apply kinematic flexibility analysis (KFA) to efficiently estimate vibrational frequencies from static pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…KFA is an efficient technique to assess functional macromolecular flexibility from static structures and to model conformational transitions. It can provide insights into how molecular functions are influenced by their flexibility 37,39–42 . For example, we previously showed and experimentally confirmed how abrogating a single hydrogen bond initiated a cascade of structural changes critical for catalysis in the enzyme isocyanide hydratase (ICH) 38 …”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…KFA is an efficient technique to assess functional macromolecular flexibility from static structures and to model conformational transitions. It can provide insights into how molecular functions are influenced by their flexibility 37,39–42 . For example, we previously showed and experimentally confirmed how abrogating a single hydrogen bond initiated a cascade of structural changes critical for catalysis in the enzyme isocyanide hydratase (ICH) 38 …”
Section: Methodsmentioning
confidence: 90%
“…It can provide insights into how molecular functions are influenced by their flexibility. 37,[39][40][41][42] For example, we previously showed and experimentally confirmed how abrogating a single hydrogen bond initiated a cascade of structural changes critical for catalysis in the enzyme isocyanide hydratase (ICH). 38 KFA represents molecules as articulated multi-body complexes with dihedral angles as revolute degrees of freedom, while non-covalent interactions such as hydrogen bonds and hydrophobic interaction are modeled as holonomic constraints.…”
Section: Mathematical Details Of the Kfa Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The utilization of kinematic flexibility analysis (KFA) offers an efficient approach in examining the flexibility of functional macromolecules, even in static structures. This technique enables the modeling of conformational transitions, shedding light on the influence of molecular flexibility on their respective functions [42][43][44][45][46][47][48]. In a previous study, we demonstrated and experimentally validated the significance of disrupting a single hydrogen bond, triggering a sequence of structural alterations crucial for catalytic activity in the enzyme isocyanide hydratase (ICH) [49].…”
Section: Kinematic Flexibility Analysismentioning
confidence: 99%